A multi-metal prussian blue analogue-alginic acid binder and a method for preparing the same
Patent Information
- Application Number
- CN202310921382.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-26
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-07-26
AI Technical Summary
[0005]针对上述存在问题或不足,为解决现有锂离子电池水性粘结剂机械强度、离子电导率不能很好兼顾的问题,本发明提供了一种多金属普鲁士蓝类似物-海藻酸粘结剂及其制备方法,通过一步沉淀(快速)与两步沉淀法(慢速)控制普鲁士蓝类似物的合成速度,更慢的合成速度有利于晶体结构的完整性,进一步的,通过海藻酸与金属离子的络合反应控制多价金属离子的浓度,调控亚铁氰根离子与金属离子之间的共沉淀反应速度,提升了普鲁士蓝类似物晶体的结晶度,为粘结剂提供了更好的离子迁移性能,在此基础上制备了金属离子交联的多金属普鲁士蓝类似物-海藻酸粘结剂,不仅具有较高的离子电导率,而且机械性能得到提升
[0018]综上所述,本发明通过两步沉淀法和高分子交联,将合成的多金属普鲁士蓝类似物作为海藻酸粘结剂中的锂离子迁移点位和交联点位以提高海藻酸体系中的锂离子电导率和力学性能,并通过海藻酸对金属离子交联反应的优先选择性进一步控制晶体的合成速度,使得复合粘结剂在保证机械强度的前提下有效提升电化学性能。
Smart Images

Figure CN116875219B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium-ion battery binder materials, specifically a polymetallic Prussian blue analogue-alginic acid binder and its preparation method. Background Technology
[0002] Lithium-ion batteries (LIBs) convert chemical energy into electrical energy through repeated insertion / extraction reactions of lithium ions between the positive and negative electrode active materials. They possess advantages such as high energy density and good cycle performance, and are widely used in portable products like laptops and electric vehicles. Lithium-ion batteries mainly consist of active materials, conductive agents, binders, current collectors, and electrolytes. The binder plays a crucial role in bonding the active materials, conductive agents, and current collectors to form a complete electrode structure. It not only uniformly disperses the active materials and conductive agents but also helps form a good electron and ion transport network, reducing electrode impedance and maintaining the structural integrity of the electrode. With the continuous development of the battery industry and the decreasing particle size of active materials and conductive agents, the capacity requirements for energy storage systems are becoming increasingly stringent. Silicon nanoparticle anodes have become the preferred anode material for high-capacity energy storage systems. Simultaneously, this has placed higher demands on the mechanical properties, conductivity, and adhesion properties of binders.
[0003] While oil-based binders offer advantages such as good thermal stability, high mechanical strength, and a wide electrochemical window, they require organic solvents like N-methylpyrrolidone (NMP), resulting in poor environmental friendliness and high cost. In contrast, water-based binders, such as carboxymethyl cellulose, styrene-butadiene rubber, alginate, and polyacrylic acid, possess excellent toughness and electrochemical stability. These binders effectively buffer strain caused by volume changes in the silicon anode material, maintain the integrity of the electrode structure, avoid the use of volatile organic solvents, and are inexpensive.
[0004] Alginic acid, a natural polymeric aqueous binder rich in hydroxyl and carboxyl functional groups, can form abundant hydrogen bonds with silicon particles, thereby improving the mechanical structure and electrochemical stability of silicon anodes. With the crosslinking of carboxyl functional groups in alginate with multivalent transition metals or polymers, the mechanical properties of the alginate network improve, but its ionic conductivity decreases significantly. Prussian blue analogues, on the other hand, possess an open framework structure that can effectively embed, store, and extract ions, enhancing ion transport capabilities. However, while common coprecipitation methods offer advantages such as speed and ease of synthesis, the electrochemical performance of Prussian blue analogues remains problematic due to the resulting crystal structure, including numerous crystal defects and high internal water content, hindering the improvement of actual ionic conductivity. Therefore, constructing a better Prussian blue crystal structure that simultaneously improves the mechanical strength and ionic conductivity of aqueous binders is a pressing issue. Summary of the Invention
[0005] To address the aforementioned problems and shortcomings, and to resolve the issue that existing aqueous binders for lithium-ion batteries cannot adequately balance mechanical strength and ionic conductivity, this invention provides a multimetallic Prussian blue analog-alginic acid binder and its preparation method. The synthesis rate of the Prussian blue analog is controlled through a one-step precipitation (fast) and a two-step precipitation (slow) method. The slower synthesis rate is beneficial to the integrity of the crystal structure. Furthermore, the concentration of multivalent metal ions is controlled by the complexation reaction between alginate and metal ions, thus regulating the co-precipitation reaction rate between ferrocyanide ions and metal ions. This improves the crystallinity of the Prussian blue analog crystals, providing better ion migration performance for the binder. Based on this, a metal ion crosslinked multimetallic Prussian blue analog-alginic acid binder is prepared, exhibiting not only high ionic conductivity but also improved mechanical properties.
[0006] A method for preparing a multimetallic Prussian blue analogue-alginic acid composite binder, the specific steps of which are as follows:
[0007] Step 1: Synthesize Prussian blue analogues with high solubility product constants via a one-step precipitation method (rapidly).
[0008] Primary metal ions were added to a 0.01–0.3 mol / L ferrocyanide ion solution, with the concentration of the primary metal ions controlled at 0.02–0.4 mol / L. After reacting for 20–30 minutes, the solution was designated as solution A. Solution A was centrifuged and dried to obtain a Prussian blue analog powder with a low solubility product constant and a crystallite size between 10 and 200 nm.
[0009] Step 2: Based on Step 1, synthesize a Prussian blue analogue with high ionic conductivity through secondary precipitation (slow).
[0010] Another secondary metal ion is added to solution A obtained in step 1, and the concentration of the secondary metal ion is controlled at 0.02–0.4 mol / L. After reacting for 1–12 hours, a new Prussian blue analog with a high solubility product constant is formed, and this solution is designated as solution B. Due to the difference in solubility product constants between the two Prussian blue analogs, the secondary metal ion can displace the primary metal ion. The Prussian blue analog prepared using this method has fewer crystal defects and higher crystallinity compared to that prepared by the traditional one-step precipitation method, effectively reducing the internal water content and significantly improving its electrochemical performance.
[0011] In step 1, the solubility product constant of the Prussian blue analog synthesized by the primary metal ions is larger than that of the Prussian blue analog synthesized by the secondary metal ions. This ensures that the primary metal ions can be slowly replaced after the secondary metal ions are added, thereby effectively controlling the synthesis rate.
[0012] Step 3: Add alginic acid to further control the crystal precipitation rate and prepare a polymetallic Prussian blue analogue-alginic acid binder.
[0013] The B solution obtained in step 2 was mixed with an aqueous alginate solution at a mass ratio of 1:3 to 1:15, with the aqueous alginate solution concentration being 1 to 8 wt%. After continuous stirring for 0.2 to 3 hours, a multi-metallic Prussian blue analogue-algin binder with multiple ions crosslinked together was obtained. Because the abundant carboxyl groups (-COOH) on the alginate chain can undergo crosslinking reactions with metal ions, thereby changing the concentration of metal ions and further slowing down the crystal precipitation rate, it is beneficial for the Prussian blue analogue crystals to form a better crystal structure within the alginate network. This results in the multi-metallic Prussian blue analogue-algin binder system exhibiting better ionic conductivity and significantly improving its electrochemical performance.
[0014] Furthermore, the primary metal ion is Mn. 2+ The secondary metal ion is Cu. 2+ Co 2+ Zn 2+ or Ni 2+ .
[0015] The polymetallic Prussian blue analogue-algin binder provided by this invention synthesizes Prussian blue analogues through a two-step method, sequentially using primary and secondary metal ions. Utilizing the different solubility product constants of the two metal ions, the Prussian blue analogues synthesized with primary metal ions have a larger solubility product constant than those synthesized with secondary metal ions. Adding secondary metal ions allows for the slow displacement of primary metal ions, effectively controlling the synthesis rate and thus producing a polymetallic Prussian blue analogue with high ionic conductivity.
[0016] On the other hand, the addition of alginic acid causes some metal ions to undergo cross-linking reactions. Secondary metal ions preferentially cross-link with alginic acid compared to primary metal ions. The metal ions can form coordinate covalent bonds with the abundant carboxyl groups (-COOH) on the alginic acid chain, which greatly improves the mechanical strength of the multimetallic Prussian blue-alginic acid binder. After adding alginic acid, the concentration of secondary metal ions can also be reduced, further slowing down the synthesis rate of Prussian blue analogs. The mechanical properties and strength of alginic acid after cross-linking with secondary metal ions can effectively suppress the volume expansion of silicon anodes, significantly improve the electrochemical performance of silicon anodes during cycling, and ensure that the crystal structure of Prussian blue analogs inside the alginic acid network is more complete and the electrochemical performance is better.
[0017] Prussian blue analogues possess an open-framework structure, enabling the insertion, storage, and extraction of ions. A better crystal structure can play a more crucial role in this process. During battery cycling, multimetallic Prussian blue analogues can provide ion migration sites for the alginate system, increasing ion transport efficiency and resulting in stable cycling performance for the multimetallic Prussian blue-alginate / silicon electrode.
[0018] In summary, this invention utilizes a two-step precipitation method and polymer crosslinking to employ synthesized polymetallic Prussian blue analogues as lithium-ion migration sites and crosslinking sites in alginate binders, thereby improving the lithium-ion conductivity and mechanical properties of the alginate system. Furthermore, the selective preferential reaction of alginate on metal ions further controls the crystal synthesis rate, enabling the composite binder to effectively enhance electrochemical performance while ensuring mechanical strength. Attached Figure Description
[0019] Figure 1 This is a schematic diagram of the structure of the polymetallic Prussian blue analogue-alginic acid / silicon electrode of the present invention;
[0020] Figure 2 SEM images of multimetallic Prussian blue analogues from the examples;
[0021] Figure 3 The diagram shows the lithium-ion conductivity of different binder systems in the examples;
[0022] Figure 4 The mechanical properties of different binder systems in the examples and comparative examples are shown in the diagram.
[0023] Figure 5 XRD patterns of multimetallic Prussian blue analogues for the examples and comparative examples;
[0024] Figure 6 Cyclic curves of the Si@Alg-PBAs electrodes in the examples and comparative examples;
[0025] Figure 7 Rate curves of Si@Alg-PBAs electrodes for the examples and comparative examples;
[0026] Figure 8 Charge-discharge curves of Si@Alg-PBAs electrodes for the examples and comparative examples; Detailed Implementation
[0027] To clearly demonstrate the purpose, technical solution, and advantages of the present invention, the present invention will be further described in detail below with reference to specific embodiments, but the implementation of the present invention is not limited thereto.
[0028] It should be noted that the illustrations provided in this embodiment are only schematic representations of the basic concept of the present invention. Therefore, the illustrations only show the key information involved in the implementation process related to the present invention, and are not drawn according to the actual implementation steps, drug types and drug dosages. In actual implementation, the types of drugs, drug dosages, drug ratios, solution concentrations and experimental parameters can be arbitrarily changed, and the actual implementation process may also be more complex.
[0029] This embodiment uses a silicon-based negative electrode for a lithium-ion battery as an example, with Mn as the primary metal ion. 2+ For ions, secondary metal ions, Cu is selected. 2+ The ion selected is Fe(CN)6, specifically the metal cyanide ion. 4- First, based on the difference in solubility product constants, a Mn-Fe Prussian blue analogue with a larger solubility product constant was synthesized; then, Cu was added. 2+ Secondary precipitation of ions and displacement of Mn 2+ Ions were used to synthesize CuMn-Fe Prussian blue analogues. Based on the sol-gel principle, most of the Cu... 2+ Ions and a small portion of Mn 2+ Ions can undergo cross-linking reactions with alginate to form coordinated covalent bonds, resulting in a more robust three-dimensional network structure and optimizing the crystal synthesis process. After preparing the binder, a novel high-ionic-conductivity multimetallic Prussian blue analog-alginate composite silicon anode was fabricated through electrode slurry preparation and coating processes.
[0030] The specific process of this embodiment includes:
[0031] Step 1: A two-step precipitation method was used to synthesize CuMn-Fe Prussian blue analogues with high electrochemical performance. The specific process is as follows:
[0032] ① Place 0.2904g NaFe(CN)6 (0.03mol / L) into a 50ml beaker, add 20ml of deionized water and a magnetic stir bar, then place the beaker on a magnetic stirrer and set the stirring speed to 500rpm to mechanically stir until the solute is completely dissolved.
[0033] ② Add 0.2028MnSO4 (0.06mol / L) to the above beaker. At this time, the solution turns into a turbid white color. Continue stirring for 25 minutes. At this time, Mn-Fe Prussian blue analogues are formed. Controlling the reaction time is the key to the crystal size of the Prussian blue analogues.
[0034] ③ Subsequently, 0.2387 g of CuCl2 (0.07 mol / L) was added to the beaker, and the magnetic stirrer was kept at 500 rpm. The solution gradually turned dark brown, and mechanical stirring was continued for 3 hours. At this point, the main product of the solution was a CuMn-Fe Prussian blue analogue, and 1 g of the mixed solution was taken out for later use. All the above experiments were conducted at room temperature. The Prussian blue analogue obtained in this example is named high ionic conductivity multimetallic Prussian blue analogue (PBAs). Figure 2 The image shown is a SEM image of the high ionic conductivity multimetallic Prussian blue analog prepared in this embodiment.
[0035] The obtained Prussian blue analogues with high ionic conductivity have a face-centered cubic structure, exhibiting a cubic appearance. The particle size ranges from 50 to 200 nm. The particle size of these Prussian blue analogues is highly dependent on the reaction time, including the reaction time between MnSO4 and NaFe(CN)6, and the reaction time after the addition of CuCl2. Controlling the reaction time is crucial for determining the grain size. The added Cu... 2+ The ions are used to replace Mn. 2+ Ions are used to control the reaction rate and, on the other hand, to cross-link with alginate to form a three-dimensional network structure. The resulting high-ionic-conductivity multimetallic Prussian blue analogues are framework structures bridged by metal ions and metal cyanide ions. The ability to accommodate different transition metal cations within the coordination framework gives them excellent ion insertion, storage, and extraction properties. Similarly, this can also be used for lithium ion extraction and insertion, which aligns with the lack of ionic conductivity in alginate binder systems.
[0036] Step 2: Preparation of a Prussian blue analogue-algin binder with high ionic conductivity based on the sol-gel method:
[0037] ① Prepare a 2wt% alginate aqueous solution (Alginate, M:G = 1:2). Take 30ml of deionized water into a 50ml beaker. Add a magnetic stir bar, place the beaker on a magnetic stirrer, set the stirring speed to 900rpm, add 0.6g of Alg to the beaker, increase the stirring speed to 1500rpm and continue stirring for 1 hour until the Alg powder is completely dissolved.
[0038] ② Take 6g of alginate aqueous solution into a glass bottle and add a magnetic stirring rod. Place the glass bottle on a magnetic stirrer and set the mechanical stirring speed to 1500rpm. Then, use a dropper to slowly add 1g of the mixed solution obtained in step 1 along the wall of the glass bottle, and keep the magnetic stirrer stirring at 1500rpm for 1 hour.
[0039] At this time, the mixed solution contains Cu 2+ Ions and Mn 2+ After the addition of alginic acid, the alginic acid preferentially reacts with Cu. 2+ The ions undergo a cross-linking reaction, resulting in free Cu 2+ As the ion concentration decreases, Cu... 2+ Ion displacement of Mn 2+ The ion rate slows down, and the crystal synthesis rate slows down again. The binder obtained in this embodiment is named a polymetallic Prussian blue analogue-alginic acid binder (Alg-PBAs).
[0040] The obtained polymetallic Prussian blue analogue-alginic acid binder mainly consists of the carboxyl group (-COOH) in alginate and Cu. 2+ Ions, Mn 2+ The three-dimensional network cross-linked structure formed by ion cross-linking and the high ionic conductivity of the multimetallic Prussian blue analog particles inside serve as ion transport sites. In addition, the abundant carboxyl groups (-COOH) in alginate can form hydrogen bonds with the silicon oxide layer on the Si surface, enabling close contact between silicon particles and binders, improving adhesion to the current collector, and ensuring the integrity of the electrode structure during cycling, thus effectively improving the cycling stability of the electrode.
[0041] Step 3: Use the binder obtained in Step 2 to prepare the silicon anode.
[0042] ①The nano-silicon powder (20nm~2μm), binder and conductive agent (Super P) are added in batches at a mass ratio of 6:2:2 and continuously ball-milled for 3 hours to ensure that the slurry is fully mixed and the original conductive slurry is obtained.
[0043] ② Apply the above slurry evenly to a flat and clean copper foil using a scraper, with a wet film thickness of 100 μm. After coating, place the silicon anode in an 80°C forced-air oven to dry for 3 hours, and then transfer the silicon anode to a 90°C vacuum oven to dry for 8 hours.
[0044] ③ Cut the above-mentioned silicon anode into circular electrode sheets with a diameter of 10 mm for later use. Weigh the sheets, record the weight, and calculate the mass of the active material. Name the obtained electrode sheet a polymetallic Prussian blue analog-alginic acid / silicon electrode (Si@Alg-PBAs). The structure of this electrode is as follows: Figure 1 As shown.
[0045] Step 4: Use the circular silicon anode obtained in Step 3 to complete the assembly of the CR2032 lithium-ion battery in the glove box.
[0046] In this embodiment, the electrolyte for the CR2032 lithium-ion battery is LB-011, and the separator is Celgard 2500. Based on the addition of a polymetallic Prussian blue analogue—alginic acid—as a binder, the lithium-ion battery is named Si@Alg-PBAs. Similarly, pure alginic acid (Alg), copper-crosslinked alginic acid (Alg-Cu), and manganese-crosslinked alginic acid (Alg-Mn) are used as binders to fabricate corresponding silicon anodes and assemble the batteries, which are named Si@Alg, Si@Alg-Cu, and Si@Alg-Mn, respectively. After the lithium batteries are assembled, they are allowed to stand at room temperature for 12 hours before subsequent electrochemical performance tests are performed.
[0047] The results of the ionic conductivity test are as follows: Figure 3 As shown, the ionic conductivity of the Alg-PBAs binder is 3.22 × 10⁻⁶. -5 Scm -1 It is significantly higher than Alg (1.60×10). -6 S cm -1 Alg-Cu (6.60×10) -6 S cm -1 Alg-Mn(2.28×10) -6 S cm -1 ) and Alg-PBAs(CP)(1.77×10 -6 S cm -1 The binder, Alg-PBAs(CP), is a Prussian blue analogue-alginic acid binder prepared by a one-step precipitation method. The two-step precipitation synthesis method and the addition of ion migration sites to the alginate system to enhance ionic conductivity employed in this embodiment are highly effective in improving the electrochemical performance of the silicon anode.
[0048] Mechanical properties of different adhesives, such as Figure 4As shown, the tensile strengths of Alg, Alg-Cu, Alg-Mn, and Alg-PBAs were 22.16 MPa, 24.11 MPa, 46.2 MPa, and 28.43 MPa, respectively, with elongations at break of 1.12%, 2.84%, 3.9%, and 2.07%, respectively. It can be seen that the tensile strength and elongation at break of the ion-crosslinked Alg are significantly higher than those of pure Alg. The crosslinking of metal ions with Alg can form strong ionic covalent bonds, thus achieving the effect of enhanced mechanical properties of the Alg system. This indicates that the three-dimensional network formed by the ion-crosslinked alginate can enhance mechanical properties and effectively alleviate the expansion stress of silicon particles during charging and discharging.
[0049] Meanwhile, X-ray diffraction (XRD) was used to test the Prussian blue analogues obtained by one-step and two-step precipitation methods, respectively. Figure 5 This demonstrates that the synthesis method has a crucial impact on the crystal structure. Specifically, the one-step synthesis method produces crystals with wider peak widths and weaker peak intensities, indicating that the two-step precipitation method produces crystals with higher crystallinity and better structural integrity. This is also the reason why the ionic conductivity of Alg-PBAs can be significantly improved.
[0050] A series of electrochemical performance tests were conducted on Si@Alg, Si@Alg-Cu, Si@Alg-Mn, and Si@Alg-PBAs batteries to obtain their cycle performance. Figure 6 ), rate performance ( Figure 7 ) and charge / discharge curves ( Figure 8 It can be observed that the cycling performance and rate performance of Si@Alg-PBAs are significantly higher than those of other control groups. This is inseparable from the enhanced mechanical properties of alginate after ion crosslinking and the addition of multimetallic Prussian blue analogues. The synergistic improvement of mechanical properties and ionic conductivity can effectively cope with the expansion effect caused by silicon particles and ensure the efficient transport and structural integrity of the ion-conducting network inside the electrode. Moreover, the experimental process and raw materials involved in this invention are almost harmless to the environment, the process is mild, and it can reduce the manufacturing cost of silicon anodes.
[0051] As can be seen from the above examples and comparative experimental groups, this invention uses a two-step method to synthesize Prussian blue analogs by successively employing primary and secondary metal ions. Utilizing the different solubility product constants of the Prussian blue analogs synthesized from the two metal ions, the addition of secondary metal ions slowly displaces the primary metal ions, thereby effectively controlling the synthesis rate and ensuring a more complete crystal structure of the Prussian blue analog within the alginate network, resulting in superior electrochemical performance. Furthermore, alginate is used to further regulate the synthesis of the Prussian blue analog. Simultaneously, the metal ions form coordinate covalent bonds with the abundant carboxyl groups on the alginate chain. Ultimately, in the binder prepared by this invention, the multi-metallic Prussian blue analog serves as both lithium-ion migration sites and crosslinking sites, significantly improving the electrochemical performance of the silicon anode during cycling while also maintaining mechanical properties.
Claims
1. A method for preparing a multimetallic Prussian blue analogue-alginic acid composite binder, characterized in that, The specific steps are as follows: Step 1: Synthesize Prussian blue analogues with high solubility product constants via a one-step precipitation method; Add primary metal ions to a 0.01–0.3 mol / L ferrocyanide ion solution, and control the concentration of primary metal ions at 0.02–0.4 mol / L. After reacting for 20–30 minutes, the solution is designated as solution A. After centrifuging and drying solution A, a Prussian blue analog powder with a low solubility product constant and a crystallite size between 10 and 200 nm is obtained. Step 2: Based on Step 1, a Prussian blue analogue with high ionic conductivity is synthesized by secondary precipitation; Another secondary metal ion is added to solution A obtained in step 1, and the concentration of the secondary metal ion is controlled at 0.02-0.4 mol / L. After reacting for 1-12 hours, a new Prussian blue analog with a high solubility product constant is formed, and this solution is designated as solution B. In step 1, the solubility product constant of the Prussian blue analog synthesized by primary metal ions is larger than that of the Prussian blue analog synthesized by secondary metal ions. Step 3: Mix the B solution obtained in Step 2 with an alginate aqueous solution at a mass ratio of 1:3 to 1:15, where the concentration of the alginate aqueous solution is 1 to 8 wt%. After stirring continuously for 0.2 to 3 hours, a multi-metallic Prussian blue analogue-alginate binder with multiple ion crosslinking is obtained.
2. The preparation method of the polymetallic Prussian blue analogue-alginic acid composite binder as described in claim 1, characterized in that: The primary metal ion is Mn. 2+ The secondary metal ion is Cu. 2+ Co 2+ Zn 2+ or Ni 2+ .
3. A multimetallic Prussian blue analogue-alginic acid composite binder, characterized in that: Prepared using the method described in claim 1 or 2.
Citation Information
Patent Citations
Aqueous binder based on alginic acid-Prussian blue, and preparation method thereof
CN113823796A
Preparation process of high-density and high-conductivity Prussian composite material
CN116314711A
